Dicrostonyx groenlandicus - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
34. Nearctic Collared Lemming Dicrostonyx groenlandicus French: Lemming du Groenland / German: Nordlicher Halsbandlemming / Spanish: Lemming neértico de collar Other common names: Bering Collared Lemming, Greenland Collared Lemming, Northern Collared Lemming, Northern Hoofed Lemming, Northern Varying Lemming Taxonomy. Mus groenlandicus Trail, 1823, Jamesons Land, Greenland. Dicrostonyx groenlandicus is in the subgenus Dicrostonyx. Opinions on the number of species of collard lemmings varied in the past from a single species (D. torquatus) to the current seven species. Taxonomic scope of D. groenlandicus is still not generally accepted. Some authors regard vinogradovi as independent species; others include nelsoni, nunatakensis, richardsoni, and unalascensis under groenlandicus. Phylogeographic analyses retrieved two clusters among Nearctic populations, separated by the Mackenzie River. Six subspecies recognized. Subspecies and Distribution. D.g.groenlandicusTrail,1823—ENunavut,includingEQueenElizabethIs,PrinceofWalesI,SomersetI,NBaffinI,andSouthamptonI(Canada)andGreenland. D.g.clarusHandley,1953—WQueenElizabethIs. D.g.kilangmiutakR.M.Anderson&Rand,1945—NYukon,NorthwestTerritories,andWNunavut(NWCanada),includingBanks,Victoria,andKingWilliamIs(SWCanadianArcticArchipelago). D.g.lentusHandley,1953—SBaffinIs. D.g.rubricatusJ.Richardson,1839—NAlaska. D. g. vinogradovi Ognev, 1948 — Wrangel I (Russia). Descriptive notes. Head-body 113-151 mm, tail 11-22 mm; weight 52-114 g. Average weight of the Nearctic Collared Lemming is greater in years of peak abundance than in intermediate years. Winter morphs are significantly longer, heavier, and rounder than summer morphs. The Nearctic Collared Lemming is chunky; it has a short tail and relatively large head. Ears are reduced to low folds of skin and entirely concealed in fur. Feet are short and broad, with densely haired soles and palms and five digits on each. Claws of third and fourth front digits are normal size during summer but enlarge in winter. Winter claws are c.1 ...